Critical Thinking Skills Development across Semesters in Nursing Students: A Cross-Sectional Study - Adelia, Gita; Alwi, Fahrizal; Asyikin, Nur; Pérez , Esperanza Zurigue; Malfasari, Eka; Putri, Veni Dayu; Arfina, Angga; Locsin, Rozzano C.; Yoder, Linda H. (Jurnal Berita Ilmu Keperawatan, 2026)
Critical thinking is a fundamental skill in nursing education that plays a crucial role in supporting professional responsibilities, enhancing service quality, and improving nursing performance in the modern era. This study aimed to analyze the dimensions of critical thinking among nursing students and assess the development of critical thinking skills across different academic semesters in the Bachelor of Nursing program at the Faculty of Nursing, IKes Payung Negeri Pekanbaru. A cross-sectional quantitative design was employed, involving 264 nursing students selected through stratified random sampling to ensure proportional representation across academic semesters. Data were collected using the Nursing Critical Thinking in Students Questionnaire (N-CT-4), which measures four dimensions of critical thinking. Descriptive and inferential statistical analyses were conducted using SPSS software, with ANOVA employed to examine differences in mean scores among students from different academic semesters. The Intellectual and Cognitive dimension had the highest mean score (M = 131.99, SD = 24.259, range = 70–176), while the Technical dimension had the lowest (M = 18.09, SD = 3.773, range = 8–24). ANOVA results indicated an upward trend in the Intellectual and Cognitive scores, increasing from 130.2 in the 3rd and 5th semesters to 136.5 in the 7th semester; however, this difference was not statistically significant. Although critical thinking skills, particularly in the cognitive domain, showed improvement across semesters, the progression was not statistically significant. These findings underscore the need for more practical, practice-based learning strategies to enhance critical thinking competencies meaningfully. Further longitudinal studies are recommended to evaluate long-term development and the impact of educational interventions.